Teachers' Expertise and the Use of Music to Develop Language Skills in Primary Schools in Nigeria - Osita, Dr. Femi (American Journal of Arts, Social and Humanity Studies, 2023)
Purpose: The purpose of the study was to establish the extent to which teachers use music to develop children's language skills in primary schools in Nigeria. Methodology: The paper used a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. Findings: The study concluded that that teachers' teaching experience influenced their use of music to teach language skills. Unique Contribution to Theory, Practice and Policy: The school management should recruit fully trained teachers in schools. In addition, school managers should develop pre-service and induction courses for their language teachers on musical skills. This is because majority of teachers who were using music could not adequately and relevantly teach language skills to learners.